The Role of Learners’ Native Language in EFL Self-Efficacy Beliefs: an Exploratory Study - Blake Turnbull (Journal of Linguistics and Language Teaching)
Many scholars agree that judicious use of learners’ native language (L1) can be advantageous in the language (L2) classroom; however, the role of the L1 in students’ beliefs about self-efficacy has received little attention in the literature thus far. Through the use of a questionnaire, this paper examines the beliefs of university-level Japanese EFL students regarding the use of the L1 (Japanese) and its role in self-efficacy in L2 (English) learning. The major findings show that Japanese university-level EFL students believed the use of Japanese may help to improve their English reading and writing skills more than their speaking and listening skills, as well as for the learning of grammar and vocabulary in particular. Suggestions about what university EFL educators can do are also provided.